QUIANTITATIVE CHARACTERSTICS OF BLOOD PLATELETS IN CORRECTION OF ACUTE BLOOD LOSS BY 3-OXYPYRIDINE DERIVATIVE AND IRON PREPARATION - Vazhnichaya, Ye.M. (World of Medicine and Biology, 2012)
In the experiments in albino male rats it is shown that iron preparation ferrum-lek (0,075 ml/kg) normalizes the count of blood platelets (PLT) and thrombocrit (Pct) in 3 hrs, but produces the lowering of PLT in 24 hrs after the loss of blood. Mexidol (2-ethyl-6-methyl-3-oxypyridine succinate) in a dose of 100 mg/kg co-administered together with ferrum-lek potentiates the normalizing influence of iron preparation in early period after the blood loss and eliminates the decrease of blood platelets count caused by it in 24 hrs after the extraction of blood.
Keywords: blood loss; blood platelets; mexidol; 3-oxypyridine; iron preparation